Effect of Ti and Cr on dispersion, structure and composition of oxide nano-particles in model ODS alloys. (15th September 2015) - London, A.J.; Santra, S.; Amirthapandian, S.; Panigrahi, B.K.; Sarguna, R.M.; Balaji, S.; Vijay, R.; Sundar, C.S.; Lozano-Perez, S.; Grovenor, C.R.M.
Abstract: Three model ODS alloys (Fe–0.3Y2 O3, Fe–0.2Ti–0.3Y2 O3 and Fe–14Cr–0.2Ti–0.3Y2 O3 ) were prepared by ball milling and then hot extrusion to study the effect of Ti and Cr on the size, distribution, crystal structure and composition of the nano-oxide particles. All alloys were characterized by high resolution transmission electron microscopy (HRTEM), atom probe tomography (APT) and synchrotron-X-ray diffraction (S-XRD) to determine the distribution, structure and composition of the oxide nanoparticles samples. The median particle sizes were 9.6 nm, 7.7 nm and 3.7 nm for the Fe–Y2 O3, Fe–Ti–Y2 O3 and Fe–Cr–Ti–Y2 O3 alloys, respectively, so the presence of Ti resulted in a significant reduction in oxide particle diameter and the addition of Cr gave a further reduction in size. In the Fe–0.3Y2 O3 alloy, the particles are found to be bcc Y2 O3, whereas in the other two alloys (Fe–Ti–0.3Y2 O3 and Fe–Cr–Ti–Y2 O3 ), the oxide particles were found to be structurally consistent with both orthorhombic Y2 TiO5 and fcc Y2 Ti2 O7 . Detailed APT studies showed Cr shells around oxide particles of all sizes in the Fe–Cr–Ti–Y2 O3 alloy, that a range of cluster compositions are present and that the particle chemistry varies with cluster size. We show that the addition of Cr has a strong effect on both the size and stoichiometry of the particles.